2013
DOI: 10.1590/s1983-14472013000200018
|View full text |Cite
|
Sign up to set email alerts
|

Produção da subjetividade do enfermeiro e a tomada de decisão no processo de cuidar

Abstract: This study aimed to understand the relationship between Nurse's production of subjectivity and the decision-making in the process of Nursing care. A qualitative design of research was conducted. The investigation was carried out with twelve nurses who work at the Associação de Caridade Santa Casa do Rio Grande, a hospital located in Rio Grande, RS, Brazil. For data collection, focus group technique was used, three meetings were conducted in december 2011. The results were presented in semantic categories: Capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
7
0
7
Order By: Relevance
“…On the other hand, the participants revealed that the subjectivity and autonomy of Nursing is still permeated by the relation of submission to medical authority. According to these findings, another study aimed at understanding the relationship between nurses' subjectivity production and decision-making in the care process indicated that dominance and subordination relations still prevail, which lead to a process of subjection that interferes in the decision of the nurse to allow or not to think, question, occupy the different spaces and exercise their autonomy, as subject (2) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the participants revealed that the subjectivity and autonomy of Nursing is still permeated by the relation of submission to medical authority. According to these findings, another study aimed at understanding the relationship between nurses' subjectivity production and decision-making in the care process indicated that dominance and subordination relations still prevail, which lead to a process of subjection that interferes in the decision of the nurse to allow or not to think, question, occupy the different spaces and exercise their autonomy, as subject (2) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of relations of domination and subordination entails a process of subjection, which interferes with the decision of the nurse to allow or not to think, question, occupy the different spaces and exercise their autonomy as a subject. Also, it can be expressed by the patient and his/her family when the nurse, in the exercise of his/her autonomy, assumes an arbitrary position, placing them in a situation of submission, without considering the possibility of sharing decisions in the practice of care; (re)producing subjectivities that meet the "good patient" (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only in this way, the decision-making becomes effective from the awareness face the reality in which we are inserted. 13 Despite the exercise of group coordination, the nurse should have the skill to make decisions, define tasks and organize the work. In addition, its operationalization is intrinsic to proper communication, as requires the instrumentalization of professionals regarding attitudinal skills that reflect in the good relationship among the integrant members of the team.…”
Section: Professional Competencementioning
confidence: 99%
“…Although domination and exploitation mechanisms are identified to which they are submitted, they experience a feeling of failure and inferiority that keeps and prevents them to counter the established. 11,12 A professional exercise that prioritizes the demands and institutional weaknesses to their professional skills, affect the identity and appreciation of the profession, and generate a psychic and work overload, compromising the quality of care. Nursing seems to need to free up a conception of responsibility for all, claiming and assuming its space with the definition and demonstration of its roles.…”
Section: )mentioning
confidence: 99%